Molecular Mechanisms of Iron and Heme Metabolism - Dutt, Sohini; Hamza, Iqbal; Bartnikas, Thomas Benedict (Annual review of nutrition, 2022)
An abundant metal in the human body, iron is essential for key biological pathways including oxygen transport, DNA metabolism, and mitochondrial function. Most iron is bound to heme but it can also be incorporated into iron-sulfur clusters or bind directly to proteins. Iron's capacity to cycle between Fe and Fe contributes to its biological utility but also renders it toxic in excess. Heme is an iron-containing tetrapyrrole essential for diverse biological functions including gas transport and sensing, oxidative metabolism, and xenobiotic detoxification. Like iron, heme is essential yet toxic in excess. As such, both iron and heme homeostasis are tightly regulated. Here we discuss molecular and physiologic aspects of iron and heme metabolism. We focus on dietary absorption; cellular import; utilization; and export, recycling, and elimination, emphasizing studies published in recent years. We end with a discussion on current challenges and needs in the field of iron and heme biology.